Diagnóstico de tuberculose latente em pessoas com artrite reumatóide, através dos testes tuberculínico e interferon - gamma release assays - Pereira, Ana Maria (2011)
The use of anti-TNF-α biologic agents to treat rheumatoid arthritis (RA) is implicated in the increase of tuberculosis (TB) incidence, requiring caution in its prescription. Thus, it is necessary to screen TB before beginning the anti-TNF-α treatment. RA patients show T lymphocyte dysfunction which may harm the late cutaneous response to tuberculin test skin (TST). More recently, other tests, ex vivo, have been used to diagnose latent TB (LTB), these tests are IGRAs (Interferon - Gamma Release Assays), which may be useful to diagnose LTB in RA patients. Thus, the author set out to undertake a comparative crosssectional analysis between RA patients and a healthy comparison group (without RA), in relation to the positivity of tests to diagnose LTB – PPD RT23 QuantiFeron-TB Gold In Tube (QTF-TB GIT) – as well as a comparison among tests. And make a systematic review of the positivity and agreement between TT and IGRAs in patients with RA, with the aim of identifying the results which used TT and IGRA inn populations with RA. The review used the LILACS, Scielo, Cochrane and Medline sources with pre-defined descriptors in Portuguese, English and Spanish, having accepted publications in these languages. The description of the methodological characteristics of the studies was made, the results of the tests in each study were presented with their respective statistical analyses. The analyses of statistical agreement among tests were also presented. The level of significance adopted was 0.05. After the exclusion of the articles which were not eligible, 19 publications were selected for analysis. No uniformity among the studies included in the review was found in relation to the methodological characteristics. The design was mostly comparative, 3 were cross-sectional and one was longitudinal coorte, the sample size in the RA group varied between 25 and 112 subjects. The composition of the comparison group also varied. Healthy subjects, subjects with other rheumatic diseases and even patients with tuberculosis were part of the groups. The tests used, both PPD and IGRAs, were of different types. No uniformity found in relation to the tests results, be it in the proportion of positivity in the RA group, which varied between 10,4% and 69,7% for the TT and 6,9% to 44,6% for the IGRAs or in the difference or similarity with comparison groups. The agreement between the TT and IGRAs was analyzed in a few studies which proved contradictory. Regarding the study conducted by the author in patients with RA in Espírito Santo (ES), the ≥ 5mm value was adopted for the reactor TT for the RA group and the ≥10mm value was adopted for the group without RA. Chi-Square tests were used for the qualitative variables and tStudent tests for the quantitative, to compare groups with and without RA. As for the RA group, it was stratified by conditions: activity of disease and immunosuppression by treatment, Fisher’s exact test was used for the activity of the disease and Chi-Square for immunosuppression. The Kappa test was used to statistically analyze the agreement between PPD RT23 and QTF-TB GIT and the McNemar test was used for disagreement. The value of significance for p was p ≤ 0.05, in all tests. The TT was reactive in 40.8% in the group with RA and 25% in the group without (p = 0.187) and the QTF-TB GIT was positive in 2 (4%) of the group with RA and 3 (7.1%) in the group without RA (p = 0.5078). No significant difference was found for reactivity to TT in RA when compared with strata with or without the disease in action (0,64). 11 However, a significant difference was found for the immunosuppressed and not immunosuppressed strata, with a better response to the not immunosuppressed group (p=0,032). The groups with and without RA did not show statistically significant agreement between the 2 tests (K = 0,116; p = 0,082 (RA); K = 0,217; p = 0,083 (without RA)). A statistically significant disagreement was found for both groups with McNemar test (p = 0,001 (RA); p = 0,039 (without RA). When the total sample was analyzed (with RA + without RA), a low but statistically significant agreement was found between tests (K = 0,146; p = 0,024), and also a significant disagreement (p = 0,001). Conclusion: The systematic review showed great heterogeneity among studies which does not enable conclusions regarding the performance of TT and IGRAs in people with RA, due to the lack of consensus among results. The study with patients with RA in ES did not show any difference between groups with and without RA in relation to reactivity to TT, as well as positivity of QTF-TB GIT. The activity of the disease did not interfere with the response to the TT, nevertheless the treatment immunosuppressor did. So as to better assess the usefulness of the tests studied in people with RA, more longitudinal and prospective studies are needed, in populations with different prevalence levels and vaccine coverage for TB, and with stratified sample for characteristics of RA such as: activity and severity of disease and level of immunosuppression by treatment.